Civil society engagement with water governance at a local government scale in South Africa - Weaver, Matthew James Thanduxolo (Rhodes University, Faculty of Science, Department of Environmental Science, 2019)
The South African state's ideological commitment to a participatory approach to managing water resources and delivering services in a way that includes all stakeholders warrants critical analysis.Realising this ideological commitment has proved challenging, due largely to the complex historical, political, social, and environmental context of integrated water resource management (IWRM) in South Africa. The overarching aim of this study was to explore and expand the learning of civil societyparticipating in water governance processes at a local government scale. To address this aim a single, in-depth, four-year case study into civil society participation in water governance in the Makana Local Municipality in the Eastern Cape Province of South Africa was conducted between 2014 and 2018. The case study comprised two research phases. Both phases of the research were conducted using an adaptive transdisciplinary and participatory action research approach underpinned by General Complexity Theory. Located at the research-practice interface, the study sought to be transformative and advance both scientific research and societal goals. Qualitative research methods and inductive and deductive modes of inference were used to collect and analyse the data respectively. In the first phase of the study, a Communities of Practice theoretical framing was adopted to investigate the emergence, practice and learning of a civil society organisation (CSO), Water for Dignity (WfD), in response to household water service delivery issues in the municipality. This phase served to build an understanding of factors that enabled and constrained the practice of WfD in addressing local water service issues, and of their role as social learning agents in building water-related knowledge in their community. As participation with the first civil society organisation fragmented, the opportunity arose for local government, the National Department of Water and Sanitation and civil society to co-engage. This opened up the second phase of the research during which the role of a multi-stakeholder platform, the Makana Water Forum (MWF), in enabling democratic water governance was investigated. The MWF was South Africa's first catchment management forum with an integrated water service and water resource management agenda. In this phase, the study drew on interventionist methodology, Change Laboratory, from Cultural Historical Activity Theory (CHAT) to 1) describe the historical development, composition and shared purpose of the MWF multi-activity system constellation; and to 2) guide participants through seven learning actions (expansive learning cycle) to identify, analyse, model and implement remedial actions to problematic aspects (contradictions) of the MWF practice. Participants of the Change Laboratory workshops built their individual and collective transformative agency (deliberate actions to transform a problematic situation) as they navigated the expansive learning process. The development of this agency was identified through a micro-analysis of agentive talk. The two phases served to advance the exploration of civil society participation from informal participation to address water issues, to formal participation in water governance processes at a local government scale. Findings from the first phase of the research revealed that dedicated and sustained support of partners with distributed expertise and the highly motivated core members of WfD enabled the practice and emergence of the civil society organisation. However, factors such as poor internal leadership, power dynamics between supporting partners, socio-economic constraints and a deeply embedded lack of agency were found to be key constraining factors to WfD's practice. Findings revealed that learning at WfD team level occurred in four ways, through learning as belonging, learning as doing, learning as experiencing and learning as becoming. The WfD CSO was able to catalyse social learning related to personal water rights; and best practices for improving water quality and water conservation in their wider community of practice. Social learning was fostered mainly through structured citizen engagements offered by WfD. The research provides evidence that civil society organisations can play an important role in bridging water-related knowledge gaps and can foster active citizenship in South African communities. However, despite significant inputs of support and resources through the engaged transdisciplinary research process, the practice and learning outcomes of WfD had a marginal transformative impact on improving the citizen's every-day water service experiences. Findings from the second phase of the study revealed the MWF to resemble a multi-activity system constellation with a multiple, partially overlapping. interests related to the management of water. The establishment, function and contradictions constraining the function of the MWF were influenced by past cycles of participatory water governance-related activity and practice at national and local scales. Through the Change Laboratory process, 25 contradictions were identified that appeared to constrain the ability of the MWF to enable inclusive and meaningful participatory water governance. Through a process of expansive learning, participants sought to overcome three sets of contradictions grouped as Problem Themes: lack of clear focus of the MWF; representation, representivity and nonattendance; and the MWF relationship with the Makana Local Municipality. Remedial actions modelled and those enacted have improved aspects of the function of the MWF (such as diversified modes of engagement and a more focussed agenda) but have only resulted in incremental shifts towards enabling improved participatory practice, most markedly in building a collaborative relationship and trust between the MWF members, municipal and government officials. The microanalysis of agentive talk revealed seven different expressions of transformative agency. Constraining socio-economic and political conditions and the limited capacity of the coordinating committee of the MWF hindered the development of transformative agency to the extent to which concrete actions were implemented. Findings further revealed that contextualising a Change Laboratory process within the adaptive cycle of a complex social-ecological system, and the particular opportunity context the system presents, could inform the enactment of agency and its potential impact on the transformation of the system. The intervention with the MWF was too short a process to clearly observe the effects of transformative actions on the sustainability of the Makana Local Municipality water system. However, long-chain transformative agency through the development of one-on-one engagements, learning journeys and a reflexive component to the MWF engagements could support transformative pathways to sustainability in the municipality and water management system. The study contributes in-depth insight into the key role of learning as a catalyst in transformative processes. Learning improves the collaborative and adaptive capacity of people, and therefore, water management institutions, to manage explicitly for the complexity inherent in "complex" socialecological systems. It provides empirical evidence as to what enables and constrains "real" participation and learning in grass-roots water governance processes in the context of a shifting national drive towards a more adaptive and developmental Integrated Water Resource Management approach. It further provides methodological contributions to 1) the application of the Change Laboratory method with multi-activity system constellations in developing world contexts and 2) value and limitations of extended and engaged transdisciplinary research. Lastly, it provides practical recommendations to the establishment and sustainable function of both community-based CSOs and multi-stakeholder platforms engaging in water governance processes.
Keywords: Government accountability -- South Africa; Civil Society -- South Africa; Political participation -- South Africa; Local government -- South Africa; Water supply -- Management; Water resources development -- South Africa; Water quality management -- South Africa